2020
DOI: 10.1371/journal.pone.0240546
|View full text |Cite
|
Sign up to set email alerts
|

The effects of taxing sugar-sweetened beverages in Ecuador: An analysis across different income and consumption groups

Abstract: To analyze the effects of taxing sugar-sweetened beverages (SSBs) in Ecuador, this study estimates a Quadratic Almost Ideal Demand System model using data from the 2011-2012 National Survey of Income and Expenditure for Urban and Rural Households. We derive own-and cross-price elasticities by income quintiles and consumption deciles for five beverages, including two types of sugary drink: (i) milk, (ii) soft drinks, (iii) water, (iv) other sugary drinks, and (v) coffee and tea. Overall, results show that a 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 49 publications
(116 reference statements)
1
20
0
Order By: Relevance
“…This means that the results can only be compared with foreign studies. The own-price elasticities derived for SSB appears to be like those obtained by other authors, i.e., Schmacker & Smed (2020) results for Denmark (-1.30), Segovia et al (2020), results for Ecuador (-1.35), and Guerrero-López et al (2017) for Chile (-1.37).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This means that the results can only be compared with foreign studies. The own-price elasticities derived for SSB appears to be like those obtained by other authors, i.e., Schmacker & Smed (2020) results for Denmark (-1.30), Segovia et al (2020), results for Ecuador (-1.35), and Guerrero-López et al (2017) for Chile (-1.37).…”
Section: Discussionsupporting
confidence: 85%
“…The latest empirical studies of the possible consequences of introducing a "sugar tax" concern many countries, e.g. Australia (Blake et al, 2019;Miller et al, 2019), Brazil (Claro et al, 2012), Chile (Caro et al, 2017b;Guerrero-López et al, 2017), Colombia (Caro et al, 2017a;Vecino-Ortiz & Arroyo-Ariza, 2018), Denmark (Bødker et al, 2015;Schmacker & Smed, 2020;Smed et al, 2016), Ecuador (Paraje 2016;Segovia et al, 2020), France (Bernardi et al, 2016), Hungary (Bíró, 2015), Mexico (Barrientos-Gutierrez et al, 2017;Colchero et al, 2015), South Africa (Manyema et al, 2014), UK (Briggs et al, 2013;Breeze et al, 2018;Cornelsen et al, 2019), or the USA (Cawley et al, 2019;Dharmasena & Capps, 2012;Finkelstein et al, 2010;Jithitikulchai & Andreyeva, 2018;Lakkakula et al, 2016;Lin et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial for households to not only consume adequate amounts of food but also safe and diversified foods. In Ecuador, at the national level, it is estimated that around 30% of the population has an excessive consumption of carbohydrates [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on substitution and complementary effects of an SSB tax has been inconclusive. While substitution to other high-calorie beverages such as milk (16,40) and fruit juices (41) was found in some studies, others reported no substitution to other beverages (42) or substitution to low-calorie beverages such as diet soft drinks (43) , coffee and tea (37,44) . There is no evidence for substitution to sugary foods such as sweets, candies, cookies and desserts (16,37,41,42) .…”
Section: Analysed (N 130)mentioning
confidence: 99%